A Pilot Investigation of the Influence of a Passive Military Exoskeleton on the Performance of Lab-Simulated Operational Tasks. Issue 4 (1st October 2020) - Gruevski, Kristina M.; Cameron, Ian J.; McGuinness, Cerys; Sy, Adrienne; Best, Krista L.; Bouyer, Laurent; Diamond-Ouellette, Gabriel; Graham, Ryan B.; Karakolis, Thomas
OCCUPATIONAL APPLICATIONS: Military load carriage increases musculoskeletal injury risk and reduces performance, but is essential for operational effectiveness. Exoskeletons may play a role in reducing soldier burden. We found that wearing a customized passive exoskeleton during a military obstacle course decreased overall performance compared to a mass-matched control condition. Specifically, the "Stairs and Ladder" and "Hatch and Tunnel" obstacles were performed slower while wearing the exoskeleton. In contrast, similar mean completion times in the "Casualty Drag, " "Sprint" and "Agility Run" obstacles were found in both the exoskeleton and control conditions. Acceptability of equipment weight and torso stiffness were rated similarly across conditions, whereas the acceptability of overall performance was rated lowest while wearing the exoskeleton. The results of this preliminary investigation suggest that the time to complete operationally-relevant military obstacles was not improved by wearing a passive exoskeleton.